STUDY OF THE AUTOMATED PUMPING STATION WITH ITS DRIVE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Modern industrial enterprises, especially metallurgical and coking plants, include a network of pumping and compressor stations. AC motors are prime movers: squirrel-cage asynchronous motors (AC) and synchronous motors (SCM). The power of prime movers ranges from tens to hundreds to several thousand kilowatts. Throttle valves regulate the efficiency; thus, the motor rotation frequency remains constant. The energy consumption of such variable-load electric drives tends to decrease compared to the nominal values. The electromechanical industry has proposed high-power frequency converters, which has allowed the transition to low-energy electric drive systems for pumping stations: one machine is powered from the mains, and the other from a frequency converter, ensuring a predetermined pressure at the specified point in the pipeline. Schemes of different machine connections and the possibility of maintaining the power factor at the optimal level are considered.
Keywords: Pumping station; Motor power diagrams; Pressure; Dictated point; Power factor